Plant Hormone Homeostasis, Signaling, and Function during Adventitious Root Formation in Cuttings - Druege, Uwe; Franken, Philipp; Hajirezaei, Mohammad R. (Frontiers in Plant Science, 2016)
Adventitious root (AR) formation in cuttings is a multiphase developmental process, resulting from wounding at the cutting site and isolation from the resource and signal network of the whole plant. Though promotive effects of auxins are widely used for clonal plant propagation, the regulation and function of plant hormones and their intricate signaling networks during AR formation in cuttings are poorly understood. In this focused review, we discuss our recent publications on the involvement of polar auxin transport (PAT) and transcriptional regulation of auxin and ethylene action during AR formation in petunia cuttings in a broad context. Integrating new findings on cuttings of other plant species and general models on plant hormone networks, a model on the regulation and function of auxin, ethylene and jasmonate in AR formation of cuttings is presented. PAT and cutting off from the basipetal auxin drain are considered as initial principles generating early accumulation of IAA in the rooting zone. This is expected to trigger a self-regulatory process of auxin canalization and maximization to responding target cells, there inducing the program of AR formation. Regulation of auxin homeostasis via auxin influx and efflux carriers, GH3 proteins and peroxidases, of flavonoid metabolism and of auxin signaling via AUX/IAA proteins, TOPLESS, ARFs and SAUR-like proteins are postulated as key processes determining the different phases of AR formation. NO and H2O2 mediate auxin signaling via the cGMP and MAPK cascades. Transcription factors of the GRAS-, AP2/ERF- and WOX-families link auxin signaling to cell fate specification. Cyclin-mediated governing of the cell cycle, modifications of sugar metabolism and microtubule and cell wall remodeling are considered as important implementation processes of auxin function. Induced by the initial wounding and other abiotic stress factors, up-regulation of ethylene biosynthesis and signaling via ERFs and early accumulation of jasmonic acid stimulate AR formation, while both pathways are linked to auxin. Future research on the function of candidate genes should consider their tissue-specific role and regulation by environmental factors. Furthermore, the whole cutting should be regarded as a system of physiological units with diverse functions specifically responding to the environment and determining the rooting response.